(untitled) (Journal of Organizational Psychology, 2017)
This paper examines the positive impact of environmental uncertainty on performance through the mediating effects of strategic business activities, decision making style, relationships and strategic orientation. This research tests the various hypothesized relationships using a path model. A sample of 152 small firms is used to test the research model. Different variables affect a firm’s financial performance and explain about 31% of the variance. Strategic orientation is impacted by strategic business activities, relationships, and decision making style and these three variables explain over 45% of the variance. The results of the empirical analysis indicate overall support for the research model.